Selection Of Malaysia School Youth Cadet Corps Leader By Using Analytical Hierarchy Process: A Case Study At SMK Ahmad Boestamam - Nurul Huda Mohamed; Norhayati Ahmat; Nurul Akmal Mohamed; Syazwani Che Razmi; Nurul Farihan Mohamed (American Institute of Physics, 2024)
Indexed by SCOPUS